2020
DOI: 10.1371/journal.pone.0240016
|View full text |Cite
|
Sign up to set email alerts
|

Visual functions in children with craniopharyngioma at diagnosis: A systematic review

Abstract: Childhood craniopharyngioma is a rare and slow growing brain tumour, often located in the sellar and suprasellar region. It commonly manifests with visual impairment, increased intracranial pressure and hypothalamic and/or pituitary deficiencies. Visual impairment in childhood adversely affects a child's daily functioning and quality of life. We systematically reviewed the literature to provide an extensive overview of the visual function in children with craniopharyngioma at diagnosis in order to estimate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 126 publications
(459 reference statements)
0
14
0
Order By: Relevance
“…4 However, the close relationship of the tumor with the anterior visual pathway produces variable campimetric alterations 2 in 68-84%. Repka et al 5 found that 17% of patients had vision of 20/40 or worse in the better eye at diagnosis and 27% continued to have the same or worse visual acuity in the better eye postoperatively. 6 For this reason, difficulties in seeing the blackboard at school or sitting closer to the television are also brought to the consultation.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, the close relationship of the tumor with the anterior visual pathway produces variable campimetric alterations 2 in 68-84%. Repka et al 5 found that 17% of patients had vision of 20/40 or worse in the better eye at diagnosis and 27% continued to have the same or worse visual acuity in the better eye postoperatively. 6 For this reason, difficulties in seeing the blackboard at school or sitting closer to the television are also brought to the consultation.…”
Section: Discussionmentioning
confidence: 99%
“…As the most common symptom in patients with craniopharyngioma, especially in children, the prognosis of visual function is always an important focus (12). In previous clinical practice, subjective examinations such as visual acuity and visual field were mostly used, which have a learning curve, but the need to repeat the measurement many times (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the above-mentioned examinations are difficult to operate, with long examination times and high coordination requirements. It is difficult for patients to complete the examination in the early postoperative period, especially for children ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In more than 50% of patients affected by CP, visual acuity and fields can deteriorate [ 60 ], causing difficulties in scholarly activities, daily life, and self-perception [ 61 ]. We found visual impairment in 70% of our patients at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%